A stereodynamic phosphoramidite ligand derived from 3, 3′‐functionalized ortho‐biphenol and its rhodium(I) complex. Issue 11 (November 2016) - Storch, Golo; Deberle, Luisa; Menke, Jan‐Michael; Rominger, Frank; Trapp, Oliver
Abstract: Stereodynamic ligands and complexes bearing functional groups to attach chiral or achiral binding sites and auxiliaries are highly attractive due to the interesting opportunities for controlling the stereochemical outcome of enantioselective transformations. In this study we report the preparation of a 3, 3′‐functionalized biphenol (BIPOL) phosphoramidite ligand (PAm ) bearing 3, 5‐dichlorobenzoyl (3, 5‐DCB) amide binding sites for noncovalent interactions. Upon coordination to [Rh(COD)2 ]BF4 this substitution pattern directs one of the 3, 5‐DCB binding sites in close proximity of the metal center resulting in liberation of both COD ligands and the formation of a [Rh(PAm )2 ]BF4 complex. Coordination of the amide carbonyl unit was found to be reversible, since the complex acted as an active catalyst in the hydrogenation of dehydroamino acid derivatives. X‐ray crystallographic investigation revealed that the second 3, 5‐DCB unit is capable of forming noncovalent π–π interactions connecting both phosphoramidite ligands. Abstract : The stereodynamic 3, 3′‐functionalized biphenol (BIPOL) phosphoramidite rhodium(I) catalyst bearing 3, 5 dichlorobenzoyl (3, 5‐DCB) amide binding sites for noncovalent interactions shows noncovalent intramolecular π‐π interactions connecting both phosphoramidite ligands in the solid state.